Analisis Tingkat Kesehatan PT Bank Rakyar Indonesia ( Persero ) TBK Menggunakan Metode Camels Periode 2021-2025 - Rofinus Beri Thalar; Herman Rustandi (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2026)
This study aims to analyze the financial health of PT Bank Rakyat Indonesia (Persero) Tbk during the 2021–2025 period using the CAMELS method. This research employed a quantitative descriptive approach using secondary data obtained from the annual reports of PT Bank Rakyat Indonesia (Persero) Tbk for the 2021–2025 period. The analysis was conducted using the CAMELS method, which consists of Capital, Asset Quality, Management, Earnings, Liquidity, and Sensitivity to Market Risk, represented by relevant financial ratios. The results indicate that PT Bank Rakyat Indonesia (Persero) Tbk maintained a very healthy financial condition throughout the study period. This is reflected in its strong capital adequacy, sound asset quality, effective management performance, optimal profitability, adequate liquidity, and ability to manage market risk. The findings imply that the CAMELS method can serve as a comprehensive tool for evaluating bank health and provide useful information for management, investors, and regulators in making decisions related to banking performance and financial stability